2022
DOI: 10.1177/00219983221129252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle size and oxide shell on variable stiffness performance of phase-changing materials

Abstract: Phase-changing materials have recently found use as particulate fillers to engender stiffness-changing behavior in composites. In the transition from solid to liquid particles, the composite modulus can be significantly reduced, and then raised again as the particles are allowed to solidify. While the general effect of stiffness tuning in phase-changing composites has been demonstrated in a range of studies and applications, the most drastic stiffness ranges are provided by fusible metallic alloys, which are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…[ 44 ] In the case of core‐shell particles, geometrical considerations are taken into account when determining the stiffness values of particles with different sizes and shell thicknesses. [ 66 ] Assuming constant values for the elastic modulus and Poisson's ratio for the shell, the stiffness of the compressed particle should be proportional to 1/ D as observed in Figure 4b. [ 35 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 44 ] In the case of core‐shell particles, geometrical considerations are taken into account when determining the stiffness values of particles with different sizes and shell thicknesses. [ 66 ] Assuming constant values for the elastic modulus and Poisson's ratio for the shell, the stiffness of the compressed particle should be proportional to 1/ D as observed in Figure 4b. [ 35 ]…”
Section: Resultsmentioning
confidence: 99%
“…Bartlett et al [198] reported that by dispersing eGaIn in silicone elastomer, the value obtained from Equation ( 2) was E i = 129 kPa, but they found agreement between their experimental data and Equation ( 1) when E i = 320 kPa (Figure 4B). The difference in the elastic modulus of inclusions could be attributed to the presence of stiff oxide skin around the liquid metal inclusions, as studied by Lear et al [156] and Buckner et al, [202] and also the interaction between adjacent inclusions, which was not predicted in Eshelby's theory.…”
Section: Composites With Liquid Metal Inclusionsmentioning
confidence: 96%
“…[197] The reinforcing effect of the liquid-solid interface has been shown for single liquid-filled microcapsules [35] and also dispersed liquid inclusions in elastomers. [198][199][200][201][202][203] Style et al [196] postulated that to include the surface tension effect in the Eshelby equation for predicting composite elastic modulus E c , the liquid inclusions can be considered as soft elastic inclusions:…”
Section: Composites With Liquid Metal Inclusionsmentioning
confidence: 99%
See 2 more Smart Citations